Identification of fungal agents isolated from burn lesions using mycological and molecular methods in patients admitted to Velayat burn hospital in Rasht city during 2022-2023 - Pegah Ardi; Roshanak Daie Ghazvini; Seyed Jamal Hashemi; Mohammadreza Mobayen; Abolfazl Pourheidari; Sadegh Khodavaisy; Mahdi Abastabar; Zahra Rafat (Iranian Journal of Microbiology, 2024)
Background and Objectives: Fungal burn wound infections (FBWIs) are one of the most disastrous complications in burn patients. The present study investigated the incidence and the species distribution of fungal agents isolated from burn lesions and reviewed the feautures, underlying conditions, and outcomes of patients. Materials and Methods: The wounds were swabbed and cultured on Sabouraud Dextrose Agar with chloramphenicol medium. Fungal identification was performed using internal transcribed spacer (ITS) and beta-tubulin sequencing. Results: A total of 380 swab specimens were obtained. Of these, 101 patients (26.75 %) were positive in culture. Among the 101 positive cases, most isolates were from males (n= 68, 67.33%) and most of them were over 30 years old. Flame (n=38, 37.63%) was the predominant cause of burns, and previous history of ICU admission (n=35, 34.66%), presence of central venous catheter (n=25, 24.75%), and diabetes mellitus (n=17, 16.83%) were the main underlying conditions. Candida parapsilosis complex (n=36, 35.64%), and Pichia kudriavzevii (C. krusei) (n=8, 7.92%) represent the most commonly isolated species Also, 2 out of 101 patients (2%) died. Conclusion: In the present study, non-albicans Candida species were much higher frequent than C. albicans with most cases associated with Candida parapsilosis complex.